Information and Communication Technology (ICT) and libraries: Research mapping and scientometric overview with special reference to Indian research - Naik, Umesha; Prakash, E R (Library philosophy and practice, 2020)
Application of Information and Communication Technology (ICT) is of paramount importance in modern-day libraries and information centres. ICT helps in capturing, processing, storing, and communicating information. No library can still rely only on traditional printed information resources to perform effectively and efficiently (Etebu, 2010). The present study investigated the various realms of research pursued focusing on ICT with respect to libraries and made an effort to map the research scientometrically with a special reference to India. ICT and library related SCOPUS records are elicited and analysed to make a review of the research pursued by professionals in the field. A steady growth in the number of publications in the area and an increasing trend is observed during the last ten years. Most of the studies are surveys in nature conducted in libraries attached to academic institutions. ICT and its implementation, usage, skills acquired by professionals, ICT development, accessibility, its impact on individual, institution, society, evaluation are the key areas discussed in most of the publication records. There are some research areas identified by the present study to be explored by researchers world-wide and Indian researchers. Special libraries and public libraries are to be focused as the users of the libraries are multifaceted. Library Philosophy and Practice is the most preferred journal for publishing research outputs from researchers in the field and Egypt and India have the maximum number of authorships in the published papers. The comparison of ICT research areas at global level and Indian scenario enabled to identify the gaps in research at both level so that those indents to take up new researches may choose the areas on complementary way.